Importance of screening for urinary tract infection in African Black diabetics - Bah, Alpha Oumar; Diallo, Mamadou Dian Mamoudou; Kaba, Mohamed Lamine; Balde, Mamadou Cellou (African Journal of Nephrology, 2014)
<p style="margin: 4px; color: #000000; font-family: 'Merrieweather sans', sans-serif; font-size: 12.6px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: left; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-style: initial; text-decoration-color: initial;">Urinary tract infections are common and often latent in diabetic patients. The objective of this study was to determinethe frequency of urinary tract infections and the organisms responsible. <p style="margin: 4px; color: #000000; font-family: 'Merrieweather sans', sans-serif; font-size: 12.6px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: left; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-style: initial; text-decoration-color: initial;">This is a descriptive type prospective study conducted in the Endocrinology and Diabetology ward of Donka UniversityHospital. All diabetic patients hospitalised from January 3rd to April 4th 2013 were included in the study. <p style="margin: 4px; color: #000000; font-family: 'Merrieweather sans', sans-serif; font-size: 12.6px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: left; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-style: initial; text-decoration-color: initial;">Two hundred and sixty-two diabetics had been screened, 64 (24.42%) had a urinary tract infection 41 women (64%)and 23 men (36%). The average age was 56.48 16.3 years with a range of 20-90 years. Urinary tract infections weremore frequent between the ages of 45 and 74 (67.20%). Sixty patients were married, four were single. Fifty-six patientswere type 2 diabetes against eight type I diabetes. Urine test strips showed 60 cases of pyuria, 36 cases of nitruria, 21cases of proteinuria and three cases of hematuria. Organisms identified were: Escherichia coli in 31 cases (48.43%): 25women and six men; Klebsiella pneumoniae in 14 cases (21.87%): nine women and five men; Staphylococcus aureusin 11 cases (17.18%): six women and five men; and Proteus mirabilis in eight cases (12.51%): two women and six men.The clinical manifestations were: asymptomatic bacteriuria in 57 cases (89.06%); acute cystitis in five cases (7.81%); andacute urethritis in two cases (3.13%). <p style="margin: 4px; color: #000000; font-family: 'Merrieweather sans', sans-serif; font-size: 12.6px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: left; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-style: initial; text-decoration-color: initial;">Urinary infection in African diabetics is very common. It requires a systematic screening with urine test strips becauseasymptomatic types are by far the most common. This would allow early treatment and avoid serious complications.